(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The foraging activities of insect visitors on cucumber (Cucumis sativus L.) were studied. The insect visitors in decreasing order of abundance were: Formica sp.>Apis mellifera>Apis cerana>syrphids≥Apis dorstata. The activity of insects was peaked at 08.00-09.00 am. The foraging behaviour of A. mellifera was also studied. The bees spent significantly more time per flower during morning hours (sec/flower) and foraged significantly fewer flowers (7.9 flowers/min) compared to evening hours. There were significantly more nectar foragers (6.03/m²/10 min) than pollen foragers (5.16/m²/10 min). Most pollen foragers were observed during morning hours (6.59/m²/10 min) whereas nectar foragers were most active during noon hours (6.63/m²/10 min). Highest fruit set was observed in hand pollination (70.68%). Percentage of misshapen fruits was maximum in without honey bee pollination (24.35%). Without honey bee pollination resulted in significantly lowest percentage of healthy fruits (75.25%). Hand pollination ranked highest among the three forms of pollination in respective of fruits (985.13 g), number of seeds per fruit (425.22), fruit diameter (27.1 cm), fruit length (26.7 cm) and weight of 1000-seeds (28.64 g). J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 81-88